A critical review on biochar for enhancing biogas production from anaerobic digestion of food waste and sludge. (10th July 2021) - Kumar, Manish; Dutta, Shanta; You, Siming; Luo, Gang; Zhang, Shicheng; Show, Pau Loke; Sawarkar, Ankush D.; Singh, Lal; Tsang, Daniel C.W.
Abstract: The conversion of food waste and sludge into biogas via anaerobic digestion technology is gaining attention in recent years, which plays a significant role in waste valorization into bioenergy and promotes environmental sustainability. Biochar is a carbonaceous material produced via thermochemical conversion of biomass waste, and tailoring biochar for diverse environmental applications adheres to the principle of circular economy. The emerging application of biochar as an additive in the anaerobic digestion of food waste and sludge has been intensively investigated in the last few years. However, a comprehensive understanding of multifunctional roles of biochar and its mechanisms in the production of biogas via miscellaneous/complex anaerobic digestion process is yet to be attained. This review scrutinizes the key roles of biochar as an additive and emphasizes the influences of biochar characteristics on the anaerobic digestion processes and their capability to address the foremost challenges. This review also evaluates the techno-economic and environmental impacts of biochar synthesis and its emerging application for biogas production via anaerobic digestion to make the integrated process more economical and environmentally sustainable, and identifies challenges and prospects for future studies. Graphical abstract: Image 1 Highlights: Biochar manifests tunable physicochemical properties for diverse applications. Biochar facilitates efficient anaerobic digestion (AD) of food waste and sludge. Microbial functions and enzymatic activity can be enhanced by biochar addition. A closed-loop material flow can be realized by integrating AD and pyrolysis.